Swing gate generated dam-break waves. Issue 5 (3rd September 2019) - Stolle, Jacob; Ghodoosipour, Behnaz; Derschum, Caren; Nistor, Ioan; Petriu, Emil; Goseberg, Nils
ABSTRACT: The study presented herein examines the influence of a swing gate on the generation of dam-break waves. Recently, researchers have been using swing gate systems, as opposed to vertical lift gates, as swing gates can be more economical as well as simpler to design and construct. The experimental programme presented herein examines the influence of the swing gate opening time on the generation, propagation and evolution of the dam-break wave profile and hydrodynamics downstream of the gate. Wave profiles were measured at several locations downstream of the gate to determine the influence of the gate opening time on its characteristics. The gate opening time was demonstrated to have a linear dependence on the wave arrival time, likely due to the gate interference in the formation of the wave. The wave profile, however, was not found to be significantly influenced by the gate opening time.